Perception of Young Executive with the Implementation of ‘Evohomestm’ As New Affordable Housing Concept in Malaysia - R. Musa, A.; M. Tawil, N.; I Che-An, A. (International Journal of Engineering and Technology, 2019)
The urban growth affected the soaring demand of affordable house especially in the urban area in Malaysia and affected the surge of housing price due to the low of affordable housing supply. This phenomenon not only affected the low-income group but also middle income group whom facing the financial difficulties in owning a house due to the rising cost of living in urban area. Khazanah Research Institute 2015 and Bank Negara, 2015 research indicates that housing price in Malaysia is unaffordable in all major cities in Malaysia for most middle to lower income groups. The IYRES study also showed that only 39.7 percent of youths owns a home. Young executives are trapped within the middle-income range of ages 23 to 35, earning between RM 2,000 and RM 3,000 per month. they are not eligible to buy a low-cost housing due to the requirement but at the same time, are not able to purchase medium cost property. Thus, the main objective of this study is to identify the young executiveâ€™s perception on the implementation of â€˜Evohomes TMâ€™ concept as strategy to provide the affordable housing. The results indicate young executive accepting this concept to be applied to affordable homes. Â Â